Greater Somatosensory Afference With Acupuncture Increases Primary Somatosensory Connectivity and Alleviates Fibromyalgia Pain via Insular γ‐Aminobutyric Acid: A Randomized Neuroimaging Trial. Issue 7 (31st May 2021) - Mawla, Ishtiaq; Ichesco, Eric; Zöllner, Helge J.; Edden, Richard A. E.; Chenevert, Thomas; Buchtel, Henry; Bretz, Meagan D.; Sloan, Heather; Kaplan, Chelsea M.; Harte, Steven E.; Mashour, George A.; Clauw, Daniel J.; et al.
Abstract : Objective: Acupuncture is a complex multicomponent treatment that has shown promise in the treatment of fibromyalgia (FM). However, clinical trials have shown mixed results, possibly due to heterogeneous methodology and lack of understanding of the underlying mechanism of action. The present study was undertaken to understand the specific contribution of somatosensory afference to improvements in clinical pain, and the specific brain circuits involved. Methods: Seventy‐six patients with FM were randomized to receive either electroacupuncture (EA), with somatosensory afference, or mock laser acupuncture (ML), with no somatosensory afference, twice a week over 8 treatments. Patients with FM in each treatment group were assessed for pain severity levels, measured using Brief Pain Inventory (BPI) scores, and for levels of functional brain network connectivity, assessed using resting state functional magnetic resonance imaging (MRI) and proton magnetic resonance spectroscopy in the right anterior insula, before and after treatment. Results: Fibromyalgia patients who received EA therapy experienced a greater reduction in pain severity, as measured by the BPI, compared to patients who received ML therapy (mean difference in BPI from pre‐ to posttreatment was −1.14 in the EA group versus −0.46 in the ML group; P for group × time interaction = 0.036). Participants receiving EA treatment, as compared to ML treatment, also exhibited resting functional connectivity between the primary somatosensory cortical representation of the leg (S1leg ; i.e. primary somatosensory subregion activated by EA) and the anterior insula. Increased S1leg –anterior insula connectivity was associated with both reduced levels of pain severity as measured by the BPI ( r = −0.44, P = 0.01) and increased levels of γ‐aminobutyric acid (GABA+) in the anterior insula ( r = 0.48, P = 0.046) following EA therapy. Moreover, increased levels of GABA+ in the anterior insula were associated with reduced levels of pain severity as measured by the BPI ( r = −0.59, P = 0.01). Finally, post–EA treatment changes in levels of GABA+ in the anterior insula mediated the relationship between changes in S1leg –anterior insula connectivity and pain severity on the BPI (bootstrap confidence interval −0.533, −0.037). Conclusion: The somatosensory component of acupuncture modulates primary somatosensory functional connectivity associated with insular neurochemistry to reduce pain severity in FM.